Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T16:52:02+01:00
A. (1⅘ + ¹⁹/₂₀) 2 - 6½= (1¹⁶/₂₀+¹⁹/₂₀)*2-6½ = 1 ³⁵/₂₀ * 2 - 6½ = 2 ¹⁵/₂₀*2-6½ = ⁵⁵/₂₀*2-6½=¹¹⁰/₂₀-6½= 5 ¹⁰/₂₀-6½=5½-6½= - 1
b. 9 ×(-1) : (-3) - (-4) × 2 - (-2)= -9:(-3) -(-8) = 27+8=36

c. 2× (-1,5) × 4
___________
0,4× 3× (-8)

[(2*(-1,5)*4)] ÷ [(0,4*3*(-8)] = (-3*4) ÷ (-8*1,2)= (-12)*(-9,6)=115,2
2010-03-21T17:08:31+01:00
(1i 16/20+19/20)2-6i1/2=(2i15/20)2-6i1/2=2i3/4*2-6i1/2=5i1/2-6i1/2=-1 9*(-1):(-3)-(-4)*2-(-2)=-9:(-3)-(-8)+2=3+8+2=13 2*(-1,5)*4=-12 ________ 0,4*3*(-8)=-9,6 czyli -12:(-9,6)=1,25